Current Therapy and Challenges for Neurodegenerative Diseases - Zhang, Wenduo (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Neurodegenerative diseases are a group of diseases characterized by progressive loss and dysfunction of neurons, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis, among others. Neurodegenerative diseases can be studied using epidemiology, which is the science of studying the distribution, effects and determinants of diseases, health conditions and events in a population, as well as countermeasures and measures for the prevention and control of diseases and the promotion of health. The incidence rate of a disease can be obtained by epidemiological studies, which is an indicator of the number of new cases in a population. This indicator is similar to the incidence rate and indicates the severity of the epidemic over a relatively short period of time. The incidence of neurodegenerative diseases increases with age, placing a huge burden on patients and their families. In recent years, with the deepening of research into the mechanisms of neurodegenerative diseases, scientists have gradually revealed the complex biological processes behind these diseases and developed a number of potential treatment strategies. This article will provide an overview of the current state of neurodegenerative disease research, recent advances, therapeutic method, and future challenges.